2008
DOI: 10.1111/j.2041-6156.2008.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Cash Holdings and Tax‐induced Debt Financing

Abstract: Stockpiling of liquid assets in cash decreases the possibility of a firm's falling into financial distress and becoming technically insolvent. Such stockpiling provides incentives for firms to increase their leverage because cash holdings decrease potential financial distress costs and increase target debt‐equity ratios. This paper examines whether firms' excessive cash holdings enhance an explanatory power of the marginal tax rate for the change in leverage. The results show that high‐taxed firms with excess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…As discussed in Kling et al (2014), cash holdings increase the ability of firms to cover possible operating loses emerged especially by liquidity shocks and to reach current liabilities in better conditions as an alternative of financing current assets, for example suppliers are more willing to provide trade credit to firms with higher liquidity positions. Also, as discussed in Jung and Kim (2008) study, stockpiling of liquid assets provides incentives for firms to increase their leverage because cash holdings decrease potential financial distress costs and increase target debt-equity ratios. In this sense, firms in Turkey decrease financial risks on cash conversion cycles by applying P-WCM and increase operating efficiency by gaining ability and flexibility on managing current liabilities.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed in Kling et al (2014), cash holdings increase the ability of firms to cover possible operating loses emerged especially by liquidity shocks and to reach current liabilities in better conditions as an alternative of financing current assets, for example suppliers are more willing to provide trade credit to firms with higher liquidity positions. Also, as discussed in Jung and Kim (2008) study, stockpiling of liquid assets provides incentives for firms to increase their leverage because cash holdings decrease potential financial distress costs and increase target debt-equity ratios. In this sense, firms in Turkey decrease financial risks on cash conversion cycles by applying P-WCM and increase operating efficiency by gaining ability and flexibility on managing current liabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Market leverage (LEVER) is defined as the ratio of total debt to the sum of total debt and market value of equity (e.g., Leary and Roberts, ). Firm size (Size) is the natural logarithm of total assets (e.g., Ozkan and Ozkan, ; D'Mello et al ., ; Jung and Kim, ; Joh and Kim, ). The bank debt rate (BANKD) is measured as the ratio of total bank loans to total debt (e.g., Ozkan and Ozkan, ; Jung and Kim, ).…”
Section: Model Designmentioning
confidence: 99%
“…Trade‐off theory contends that the optimal level of cash in the firm is determined by the marginal benefit and cost of cash holding (Ferreira and Vilela, ; Jung and Kim, ). Holding enough cash allows firms to avoid transaction interference due to a cash shortage; as a result, firms can save on transaction costs (Keynes, ).…”
Section: Model Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This greatly reduces the agency costs of free cash flow. While analyzing financing decisions in Korean firms, Jung and Kim (2008) reported that firms having larger cash reserves have better chance of exploiting benefits of interest tax shield in Korea.…”
mentioning
confidence: 99%